An assessment of the Young Lives sampling approach in Vietnam - Nguyen, N (2008)
This paper outlines the sampling methodology used by Young Lives in Vietnam. The Vietnam team selected study sites with a pro-poor bias using purposive and random sampling approaches. This paper assessed this sampling methodology by comparing baseline data collected in 2002 with data from two nationally representative surveys the Vietnam Household Living Standard Survey 2002 (VLSS 2002) and the Demographic and Health Survey 2002 (DHS 2002). Examination of the common variables in the different surveys – household characteristics, access to electricity and drinking water – indicates that the Young Lives sample includes households with less access to basic services and thus includes some biases. A comparison of wealth index scores reveals that Young Lives households are slightly poorer than the average Vietnamese household. These differences reflect the pro-poor sampling approach chosen by Young Lives in Vietnam. Despite these biases, it is shown that the Young Lives sample in Vietnam covers the diversity of children in the country. Therefore, while not suited for simple monitoring of child outcome indicators, the Young Lives sample will be an appropriate and valuable instrument for analysing causal relations, modelling child welfare, and its longitudinal dynamics in Vietnam.